Electrochemical and X-ray diffraction studies on polypyrrole films - Pruneanu, S.; Graupner, W.; Oniciu, L.; Brie, M.; Turcu, R.
The redox behaviour of polypyrrole (PPY)films doped with perchlorate (Clod-)or p-toluene sulfonate (TsO-)anions was studied by cyclic voltammetry. The values of the kinetic parameters I,, crA and cyc (exchange current density, anodic and cathodic transfer coefficients)were obtained using Tafel equations. We report a decrease in the lo value after each redox scan, in contrast with the cu,a ndc u,v aluesw, hich remain almost constant. We attribute this variation of the I,, value to the irreversible trapping of cations (Li+ or H+)in the polymer layer, after the eductionp rocessX. -ray diffraction measuremenetvsi denceda na nisotropicm oleculaor rganizationo f PPY (TsO- ), in contraswt ith PPY (ClO,- ), which exhibits an isotropic structure.
Keywords: REDOX KINETICS; X-RAY SCATTERING; POLYPYRROLE ANISOTROPY